EFFECT OF CITICHOLINE CO-ADMINISTRATION WITH ANTIPLATELET IN HOSPITALIZED STROKE ISCHEMIC PATIENTS - Rochmawati, Ike Dhiah; Saputra, Dosy Mulia; Rahmawati, Rosy (STIKES Rumah Sakit Anwar Medika, 2020)
Ischaemic stroke is a disease caused by the formation of thrombus or emboli in the cerebral artery. One of the most important medicines which analysed in several studies is Citicholine. The purpose of this study was to look at the effect of adding Citicholine with antiplatelets in Ischemic Stroke patients. The design used was an observational study with a retrospective approach. Patient demographics were analyzed descriptively. From the results of the study found 100 patients used as research samples. Based on the patient's characteristics, the greatest percentage was obtained in female patients, aged> 55 years and with accompanying hypertension, diabetes mellitus. After statistical analysis, there was no difference between the length of stay of patients in different age groups. Citicholine has been shown to provide better outcomes, by looking at the outcomes of patients who are totally cured compared with patients who are partially cured, statistically significant.